2019
DOI: 10.1177/1747021818819777
|View full text |Cite
|
Sign up to set email alerts
|

Cuing both positive and negative episodic foresight reduces delay discounting but does not affect risk-taking

Abstract: Humans frequently create mental models of the future, allowing outcomes to be inferred in advance of their occurrence. Recent evidence suggests that imagining positive future events reduces delay discounting (the devaluation of reward with time until its receipt), while imagining negative future events may increase it. Here, using a sample of 297 participants, we experimentally assess the effects of cued episodic simulation of positive and negative future scenarios on decision-making in the context of both del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 141 publications
7
84
1
3
Order By: Relevance
“…Previous research has shown that engaging in episodic future thinking during intertemporal choice reduces individuals' natural disposition towards immediate gratification in favor of choices with long-term benefits, attenuating DD (e.g., Peters and Büchel, 2010;Benoit et al, 2011;Daniel et al, 2013;Lin and Epstein, 2014;Dassen et al, 2016;Bromberg et al, 2017;Bulley and Gullo, 2017;Bulley et al, 2019). In most DD tasks, episodic future thoughts are instilled in intertemporal choice using online cues that point to (previously imagined) experiences to occur at the relevant task delays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that engaging in episodic future thinking during intertemporal choice reduces individuals' natural disposition towards immediate gratification in favor of choices with long-term benefits, attenuating DD (e.g., Peters and Büchel, 2010;Benoit et al, 2011;Daniel et al, 2013;Lin and Epstein, 2014;Dassen et al, 2016;Bromberg et al, 2017;Bulley and Gullo, 2017;Bulley et al, 2019). In most DD tasks, episodic future thoughts are instilled in intertemporal choice using online cues that point to (previously imagined) experiences to occur at the relevant task delays.…”
Section: Discussionmentioning
confidence: 99%
“…In the episodic cue (compared to the standard) task, individuals' preferences shifted towards future rewards, and the reduction of DD rates was associated with the vividness of the imagined future event and with increased functional coupling between the hippocampus and vmPFC and ACC regions associated with reward processing and valuation (Kable and Glimcher, 2007;Peters and Büchel, 2010;Benoit et al, 2011). The effect of episodic cueing on DD is consistently found in healthy individuals (Benoit et al, 2011;Liu et al, 2013;Lin and Epstein, 2014;Bromberg et al, 2017;O'Donnell et al, 2017O'Donnell et al, , 2018Zhang et al, 2018;Bulley et al, 2019), as well as patients with substance abuse disorders (Daniel et al, 2013;Snider et al, 2016), in whom it extends to real-world indices of impulsive choice, such as impulsive drinking or eating (Daniel et al, 2013;Dassen et al, 2016; see also Wu et al, 2017). In contrast, consistent with Peters and Büchel's (2010) finding that episodic cueing effects on DD are conditional upon the imagination of vivid future events, no episodic cueing effect has been observed in amnesic patients with hippocampal damage (Palombo et al, 2014; but see Kwan et al, 2015), who cannot construct detail-rich future events (Race et al, 2011;see also De Luca et al, 2018) to use for decisions.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the primary goals of this study were to examine whether EFT induced lower discounting rate compared to episodic recent thinking (ERT) in schizotypy and whether it was related to the magnitude of reward. Given previous studies have consistently shown that positive EFT significantly reduced discounting rate, while the effect of negative EFT was inconsistent (Bulley et al, 2019;Calluso, Tosoni, Cannito, & Committeri, 2019;Liu, Feng, Chen, & Li, 2013;S. Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
“…As to the emotional valence of the imagined events, studies consistently revealed that positive EFT significantly reduced delay discounting, while the effect of negative EFT was inconsistent (Bulley et al, 2019;Calluso et al, 2019;Liu et al, 2013;S. Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%